HUBUNGAN INTENSITAS PENGGUNAAN APLIKASI TIKTOK DENGAN POLA INTERAKSI SOSIAL TEMAN SEBAYA KELAS V B SD NEGERI 10 MANURUGE - Firdaus; Sidrah Afriani Rachman; M. Fadillah Al Hidayah (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This study is a quantitative research with a correlational design aimed to determine the relationship between the intensity of using the TikTok application and peer social interaction patterns among fifth-grade students of SD Negeri 10 Manurunge. The population of this study consisted of 28 students from the fifth grade. Data were collected using a closed questionnaire, and the data were analyzed through descriptive statistical analysis and inferential statistical analysis using SPSS version 23. Based on the descriptive analysis, the average score of TikTok usage intensity was 48.04 and the average score of peer social interaction was 48.79, both of which fall into the currently category. The results of inferential statistical analysis using Spearman’s rho test showed a significance value of 0.000 ≤ 0.05 with a correlation coefficient of 0.696. This indicates a strong positive relationship between the intensity of TikTok usage and peer social interaction patterns. Thus, the higher the intensity of TikTok usage, the higher the peer social interaction patterns of fifth-grade students at SD Negeri 10 Manurunge.